Efektivitas Penggunaan Media Sosial dalam Pemasaran Restoran: A Literature Review - Bakar, Nurunnisa Paquita Syech Abu (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
Social networking sites (SNS) have penetrated the daily lives of many people, with an estimated more than 4 billion SNS users in 2021. Currently, many restaurants use social media as a promotional tool. Many customers share their dining experiences and interact with other customers on social media. It is important for restaurant management to pay attention to the quality, message argumentation, and aesthetics of the uploaded content in order to create an emotional connection between customers and the restaurant. In order to create an effective social media strategy, it is necessary to identify and determine the platforms that suit your restaurant. This research was carried out using a qualitative approach and a literature review method for articles published in 2019 - 2023. Sources of research articles regarding the use of social media marketing in the restaurant industry were obtained by searching using the keyword "social media" combined with the keywords "restaurant" and " marketing” or “restaurant marketing” via the Remote Lib UI search database. A total of 5 articles were selected for systematic review. The results found that the types of platforms most frequently used were Facebook, Instagram, and Twitter. The use of social media is positively related to restaurant performance in the areas of finance, marketing and operations. Customers use social media to interact and voice their opinions regarding restaurant services through photos and reviews because this content is considered more objective and credible compared to information produced by restaurant owners.